Efficiency of L-arginine and L-carnitine in the Complex Treatment of Patients With Acute Myocardial Infarction and Comorbid Metabolic Syndrome - Shved M.; Pelo M. (Львівський клінічний вісник)
Introduction. According to the results of numerous studies, synergistic effects of various components of the metabolic syndrome (MS) play a major role in the development of atherosclerosis, coronary artery disease and myocardial infarction (MI), due to the formation of numerous hemodynamic, neurohumoral, immuno-inflammatory, procoagulant reactions, leading to metabolic disorders in the cardiac muscle and vascular endothelial dysfunction. These pathogenetic factors of MI development, its complications and their progression are present in all patients with MI associated with this comorbid condition. However, modern specific treatment of endothelial dysfunction and energy supply of the myocardium is not included in the relevant protocols for the treatment of MI due to the lack of sufficient evidence. Aim. Evaluation of the clinical efficiency of L-arginine and L-carnitine in the complex treatment of patients with acute MI and comorbid metabolic syndrome. Materials and methods. 82 patients diagnosed with acute MI and MS were examined and were divided into 2 groups depending on the type of treatment program. Patients were examined by the standard clinical and anamnestic examination, anthropometry with body mass index identification, determining the lipid panel parameters, myocardial necrosis biomarkers, electrophysiological state assessment of the myocardium according to ECG, Holter monitoring of ECG and blood pressure, transthoracic echocardiogram. Results and discussion. The comparative analysis of the structural and functional parameters of the heart, according to echocardiographic data of 34 patients with MI who received standard protocol treatment with the corresponding parameters in 48 patients who had received additional treatment including L-arginine and L-carnitine, showed that the size of the left atrium was significantly lower in the examined test group (p = 0.02), and slight decrease of the aorta size, the thickness of the interventricular septum, the diastolic size of the left and right ventricles, which led to the significant increase of left ventricle ejection fraction by 9,1 % (p = 0.01). At the same time, this group less frequently had an acute heart failure (p = 0.03), acute aneurysm of the left ventricle (p = 0.04), thromboendocarditis (p = 0.03), epistenocardiac endocarditis (p = 0.03) and disorders of cardiac rhythm and conductivity (p = 0.03). Conclusions. Patients with myocardial infarction and comorbid metabolic syndrome have significant disorders of the structural and functional state of the heart and its electrical instability, which is accompanied by the decreasing of myocardial contractile function, rhythm and conduction disorders, which cause the development of vascular endothelial dysfunction and violation of energy supply of cardiomyocytes. Complex treatment of patients with acute myocardial infarction and comorbid metabolic syndrome, including L-arginine and L-carnitine, can significantly increase the myocardial contractile function and ensure its electrical stability, which is accompanied by the significant frequency of decreasing life-threatening complications.